Handbook of health psychology - Baum, Andrew; Revenson, Tracey A.; Singer, Jerome E. (New York : Psychology Press, 2012)
"Considered the most comprehensive handbook in the field, this new edition reviews the latest approaches to the most critical topics in health psychology today. This edition maintains the bio-psycho-social model framework. It cuts across concepts (e.g., behavior change), populations (e.g. women's health), risk and protective factors (e.g., obesity) and diseases, making it appropriate for a variety of readers from various fields.The contributors include the top researchers and rising stars in field. Each author provides a theoretical foundation, evaluates the empirical evidence, and makes suggestions for future research, clinical practice, and/or policy. Novices to the field appreciate the accessibly written chapters, while seasoned professionals appreciate the books deep, cutting edge coverage. The second edition reflects the enormous progress that has been made in the connections among the bio-psycho-social components of health, behavior, and illness. This model has been expanded across several levels of analysis, including cultural, macro-social, and cellular factors. The 2nd edition also features: Greater emphasis on translating research into practice and policy. Two new sections on risk and protective factors for disease and another on social and structural influences that affect health such as socioeconomic status, reflect the current scholarship in the field. More on prevention and/or interventions and treatment in the applications section. The book opens with the fields central theories including a "newer" stress theory that emphasizes the interaction of biological and social systems. Part 2 reviews the mechanisms that help us explain the link between health and behavior across diseases and populations. The all new Part 3 focuses on variables that lead to the onset and progression of major diseases or that are instrumental in promoting health. These factors can be behavioral (e.g., smoking, exercise), psychological (e.g., personality, depression) or a combination of the two (e.g., obesity). Part 4, also new to the 2nd edition, highlights the social and structural influences on health. The book concludes with applications of research to specific disorders. The handbook serves as a text in graduate and/or upper level undergraduate courses in health psychology taught in a variety of departments including psychology, public health, medical sociology, medicine, nursing, and other social and allied health sciences. Because of its comprehensive and current coverage, it also appeals to researchers and practitioners in these fields"--
"Preface Since the publication of the first edition of the Handbook of Health Psychology (Psychology Press, 2001), enormous progress has been made in the connections among biological, psychological, and social components of health, health behavior, and illness. More important, scholars in the fi eld have expanded this tripartite model across even more levels of analysis, including cultural and macrosocial factors at one end and cellular factors at the other. Moreover, a new emphasis has been to translate research evidence in to practice and policy. The second edition of the handbook refl ects these changes and is quite different from the fi rst in terms of both approach and content. The 34 chapters are written by some of the top scholars in health psychology. Each author has taken seriously the task of providing a theoretical foundation, synthesizing and evaluating the empirical evidence, and contemplating how the state of the science can inform future research, clinical practice, and/or policy. The book maintains the fi rst edition's framework of the biopsychosocial model, but the choice of topics refl ects the advances that have been made in the fi eld over the past quarter century. Specifi cally, this new edition adds sections on risk and protective factors for disease and on macro-level factors that affect health. We believe that this structure more closely refl ects current scholarship in health psychology. The fi rst section, "Overarching Frameworks and Paradigms," presents the central theories that inform many areas of research within the fi eld. For example, the concept of allostatic load is a "newer" stress theory that emphasizes the interaction of biological and social systems and may explain the onset of many conditions"--
Includes bibliographical references and indexes.
Keywords: Clinical health psychology -- Handbooks, manuals, etc; Medicine and psychology -- Handbooks, manuals, etc; PSYCHOLOGY / Applied Psychology; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Clinical Psychology